Cancer survivorship : understanding the issues faced by cancer survivors : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Palmeston North, New Zealand - Hayward, Penelope Anne (Massey University, 2010)
International research on cancer survivorship has started to identify a range of issues that affect cancer survivors physically, mentally, emotionally and spiritually. These issues can be present at any time, from diagnosis, throughout treatment and for the rest of the individual’s lives. The quality of life and well-being cancer survivors depends on many interacting factors including the type of cancer they are diagnosed with, the type of treatment provided, healthcare utilisation, social support availability and use, employment status, locus of control, ethnicity and socio-economic status. The objective of this study was to investigate the influence of these factors on cancer survivor’s quality of life, health outcomes and support needs within the New Zealand population. Of particular interest is whether ethnicity might affect outcomes. It is hoped that the information provided by this study will help to inform future policy and interventions for cancer survivors. This study analysed and discussed data from the 2008 Health Work and Retirement Survey. The Health and Work Retirement Survey collected information from over 3000 participants, ranging in age from 57-72 years. This age group has an increased likelihood of cancer diagnosis but also potentially has several more years of active participation in society. Results from this study were consistent with overseas research and indicates that New Zealand cancer survivors share similar issues to those overseas. Of all the factors, socioeconomic status was found to be the largest contributor to a poorer quality of life in cancer survivors.
Keywords: Cancer patients; Cancer survivors; Psychology; Health psychology; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380107 Health, clinical and counselling psychology